Field‐Effect Transistors: Thickness‐Dependent Carrier Transport Characteristics of a New 2D Elemental Semiconductor: Black Arsenic (Adv. Funct. Mater. 43/2018). (22nd October 2018) - Zhong, Mianzeng; Xia, Qinglin; Pan, Longfei; Liu, Yuqing; Chen, Yabin; Deng, Hui‐Xiong; Li, Jingbo; Wei, Zhongming
Abstract : In article1802581, Zhongming Wei and co‐workers describe the layered crystal structure for a new 2D elemental semiconductor consisting of black arsenic (b‐As). The image also shows the Chinese character of the "As" element. The reported b‐As is more stable under ambient conditions than black phosphorous and could be obtained from natural mineral.